Respuesta :

Answer:

-6+7i-3-2i= -9+5i

Step-by-step explanation:

answer is shown

For this case we must simplify the following expression:

[tex](-6 + 7i) - (3 + 2i) =[/tex]

Applying distributive property to the terms of the second parenthesis we have:

Taking into account that:

[tex]+ * - = -\\-6 + 7i-3-2i =[/tex]

Adding similar terms:

[tex]-6-3 + 7i-2i =[/tex]

We take into account that:

Equal signs are added and the same sign is placed.

Different signs are subtracted and the major sign is placed.

[tex]-9 + 5i[/tex]

Answer:

[tex]-9 + 5i[/tex]